2022
DOI: 10.1007/s10067-022-06334-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the main causes, outcome, and prognostic factors of patients with rheumatologic diseases admitted to the medical intensive care unit in Southern Iran

Abstract: Background Systemic rheumatic diseases (SRD) are a heterogeneous group of diseases that can involve several organ systems and occasionally requires intensive care unit (ICU) admission because of severe systemic disease, life-threatening organ involvement, or complication of treatment. The objective of this study is to determine the causes, outcome, and prognostic factors of patients with rheumatologic diseases admitted in teaching medical ICUs in southern Iran. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…In a recent study of 3434 AL amyloidosis patients, 1.5% showed a positive amyloid deposition in muscle biopsy, in which 11 (22%) had amyloid muscle involvement. Myalgia, muscle weakness, macroglossia, jaw claudication, dysphagia, skeletal pseudohypertrophy, and hoarseness are common symptoms in individuals with amyloid myopathy [ 4 , 5 ]. Our patient had a gradual lower-limb muscular weakness, as well as jaw claudication.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of 3434 AL amyloidosis patients, 1.5% showed a positive amyloid deposition in muscle biopsy, in which 11 (22%) had amyloid muscle involvement. Myalgia, muscle weakness, macroglossia, jaw claudication, dysphagia, skeletal pseudohypertrophy, and hoarseness are common symptoms in individuals with amyloid myopathy [ 4 , 5 ]. Our patient had a gradual lower-limb muscular weakness, as well as jaw claudication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that shock, the use of vasopressors, the need for renal replacement, and mechanical ventilation are associated with poor prognosis [ 1 , 19 , 27 , 28 ]. In the current study, septic shock and the need for IMV were independent risk factors for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with rheumatic diseases have a higher risk and mortality rate of admission to the intensive care unit (ICU) compared to the general population (1,2). The mortality rate of ICU population with rheumatic diseases has been reported to be 30.5-48% (3)(4)(5), which was greater than that of the common ICU patients (1,6). Thus, early identification for rheumatic patients at high risk of mortality is critical to improving prognosis and optimizing healthcare resource utilization.…”
Section: Introductionmentioning
confidence: 99%